2009
DOI: 10.1016/s2255-4971(15)30151-8
|View full text |Cite
|
Sign up to set email alerts
|

Early Complications in the Orthopedic Treatment of Bone Metastases

Abstract: Objective: To assess the early complications in the orthopedic treatment of metastatic bone lesions and the factors associated with these complications. Method: There were assessed, retrospectively, 64 patients that underwent surgical treatment for bone metastases, analyzing the complications that occurred in the pre-operative and early post- operative period and associating them with the tumor origin, type of procedure done, the need of blood reposition before the surgery, the need of new surgical procedures … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 9 publications
(25 reference statements)
1
9
0
Order By: Relevance
“…The basic demographic data of patients in this study with respect to age parameters and sex distribution is in agreement with reports elsewhere of patients affected by bone metastases in general. 1,2,8,10 The slight preponderance of females over the males as well as the mean age of the patient population observed in our study is corroborated by these other reports. Such primary carcinomas as prostate, breast, kidney, lung, and thyroid cancers have been associated with high risks of metastatic bone diseases and are known to be responsible for 80% of all the metastases to the bone.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…The basic demographic data of patients in this study with respect to age parameters and sex distribution is in agreement with reports elsewhere of patients affected by bone metastases in general. 1,2,8,10 The slight preponderance of females over the males as well as the mean age of the patient population observed in our study is corroborated by these other reports. Such primary carcinomas as prostate, breast, kidney, lung, and thyroid cancers have been associated with high risks of metastatic bone diseases and are known to be responsible for 80% of all the metastases to the bone.…”
Section: Discussionsupporting
confidence: 92%
“…In the study by Yehuda et al, 10 the femur was the most common site of renal cell carcinoma metastasis requiring surgery. Also the work by Teixeira et al 1 showed that the femur accounted for 79.7% of metastatic sites requiring surgery in their patients. In both series, the proximal femur (hip) was the most common site of metastasis needing surgery.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…With advances in protocols and treatment of cancer patients and consequent increase in survival, the number of patients with bone metastases has increased, as well as the incidence of complications 1, 2, 3, 4. One of the complications often found in these patients are pathological fractures, especially in the lower limbs, which invariably affect the meta-epiphyseal region of the bone and requires joint reconstruction.…”
Section: Introductionmentioning
confidence: 99%